Financing the Agricultural Sector of the Economy and Its Impact on Sustainable Environmental Aspects - AIDAROVA, Aina; MAULENKULOVA, Gulbana; DAURBAEVA, Marzhan; KAMENOVA, Mazken; AIMURZINA, Baglan; JANBIRBAEVA, Sanim (Journal of Environmental Management and Tourism, 2022)
Features of the agricultural sector are closely related to biological and natural-climatic processes and depend on the seasonality of economic activity , i.e . directly depend on climatic factors as the main source of production of land resources, the agro-industrial complex. An analysis of the state of the agricultural sector of the economy of the Republic of Kazakhstan shows some important problems related to the influence of environmental factors on the agro-industrial complex, as well as on financial relations in this sector, based on the basic principles that reflect the objective requirements for the development of public finances and environmental relations, for the rational distribution of agricultural products, which is associated with the need for financing and rational planning for the use of investments attracted to agriculture.